Energy management system in Samui power grid with solar floating PV and battery energy storage systems - Nuttakun Makearoon; Weerakorn Ongsakul; Singh, Jai Govind; Ekbordin Winijkul; PEA-AIT Education Cooperation Project; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
This Master's thesis explores integrating renewable energy, particularly Solar Floating Photovoltaic (FPV) systems, into Thailand's power grid, with a particular focus on Samui Island. The study is propelled by Thailand's increasing electricity demand and its strategic move towards renewable energy to mitigate carbon emissions and reduce reliance on imported fuels. The research stems from a context where community opposition to traditional power plants in Thailand, mainly due to pollution concerns, makes renewable energy a more viable and environmentally friendly alternative. The research objectives include evaluating the peak load capacity of Samui's power grid, assessing the feasibility of Solar FPV systems with integrated energy storage on the island, and developing an optimized grid management system. This involves analyzing electricity consumption patterns, assessing geographical and environmental suitability for FPV installations, and using advanced simulation and optimization tools to ensure a stable, cost efficient, and sustainable power grid. The methodology employed in this study involves a thorough evaluation of the electric consumption in Samui's power grid and the energy generation potential of FPV systems in selected areas on the island. This process includes collecting electricity usage data, using PV Syst software to project solar energy production, and employing Homer Pro software for simulation. The study aims to understand the grid's current load characteristics, determine the optimal solar power output considering local environmental conditions, and evaluate the impact of integrating renewable energy sources on grid stability and efficiency. A critical aspect of the study is a load flow analysis to explore the grid's performance under various load scenarios, mainly focusing on the integration of FPVs and other renewable energy sources. In conclusion, this thesis analyses the technical and financial aspects of integrating renewable energy into Thailand's power grid. It proposes a sustainable and effective solution for enhancing power reliability and environmental sustainability on Samui Island by integrating Solar FPVs with battery storage. This approach addresses immediate power reliability challenges and aligns with global trends towards cleaner energy solutions.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Title page = Year 2023
Thesis (M. Eng.) - Asian Institute of Technology, 2023
Keywords: Storage batteries -- Thailand; Electric power systems -- Thailand; Renewable energy sources -- Thailand; Microgrids (Smart power grids) -- Thailand